Alumni Characteristics of Collegiate Recovery Programs: A National Survey. Issue 2 (3rd April 2019) - Brown, Austin M.; Ashford, Robert D.; Figley, Naomi; Courson, Kayce; Curtis, Brenda; Kimball, Thomas
ABSTRACT: Collegiate recovery programs (CRPs) support students in or seeking recovery from substance use disorders or mental health disorders while enrolled in college. Collegiate recovery has been established as a field of study since the 1970s. To date, a number of qualitative studies have been completed on the programs and students served, along with a single national descriptive survey. This pilot study is the first undertaken exploring the status (recovery, professional, and quality of life) of student alumni that engaged in undergraduate collegiate recovery programs (CRP). Results contain alumni recovery status, primary recovery supports utilized, relapse rates since graduation, and recovery capital/quality of life scores. Similar to previously published works, CRP alumni remain actively in recovery, with relapse rates only slightly higher than the national average of students currently engaged in CRPs (10.2% vs. 6.8%). Findings are preliminary evidence that collegiate recovery programs adequately prepare engaged students for future recovery and professional life.